Combinatorial Synthesis of New Pyrimidine‐ and Purine‐β‐d‐Ribonucleoside Nucleolipids: Their Distribution Between Aqueous and Organic Phases and Their In Vitro Activity Against Human‐ and Rat Glioblastoma Cells In Vitro. Issue 9 (20th August 2018) - Hammerbacher, Katharina; Görtemaker, Katharina; Knies, Christine; Bender, Eugenia; Bonaterra, Gabriel A.; Rosemeyer, Helmut; Kinscherf, Ralf
Abstract : Two series of nucleolipids, O ‐2′, 3′‐heptanylidene‐ as well as O ‐2′, 3′‐undecanylidene ketals of six β ‐d ‐ribonucleosides (type A) and partly N ‐farnesyl derivatives thereof (type B) were prepared in a combinatorial manner. All novel compounds were characterized by elemental analysis and/or ESI mass spectrometry and by UV‐, 1 H‐, and 13 C‐NMR spectroscopy. Conformational parameters of the nucleosides and nucleolipids were calculated from various 3 J (H, H), 3 J ( 1 H, 13 C), and 5 J (F, H) coupling constants. For a drug profiling, the parent nucleosides and their lipophilic derivatives were studied with respect to their distribution (log P ) between water and n ‐octanol as well as water and cyclohexane. From these data, qualitative conclusions were drawn concerning their possible blood‐brain barrier passage efficiency. Moreover, nucleolipids were characterized by their molecular descriptor amphiphilic ratio ( a.r .), which describes the balance between the hydrophilicity of the nucleoside headgroup and the lipophilicity of the lipid tail. All compounds were investigated in vitro with respect to their cytostatic/cytotoxic activity toward human glioblastoma (GOS 3) as well as rat malignant neuroectodermal BT4Ca cell lines in vitro . In order to differentiate between anticancer and side‐effects of the novel nucleolipids, they were also studied on their activity on differentiated human THP‐1 macrophages. Abstract :